Building Energy Index (BEI): A study of government office building in Malaysian Public University - Tahir, Mohamad Zamhari; Jamaludin, Roslan; Mohd Nawi, Mohd Nasrun; Baluch, Nazim Hussain; Mohtar, Shahimi (Taylor’s University, 2017)
Energy consumption in developing countries such as Malaysia is certainly growing in line with current economic growth and development of commercial as well as residential areas. Thus, various initiatives can be seen, in particular by the role of the government in ensuring the optimum and efficiency usage of energy in the building. Therefore, MS1525 standard is a standard that takes into account the energy efficiency of a building as a reference to determines to what extent the building meets the current standard. Then, this paper presents the Building Energy Index (BEI) for the Chancellery building in Universiti Utara Malaysia (UUM). The aim is to study BEI for the buildings whether this building achieved the standard requirement. The objective of the study was achieved by collecting data of monthly energy usage, gross floor area of the buildings and calculating BEI to get actual results. Preliminary audit which involves a brief review of utility and building operation, observation and a walkthrough in the buildings are used. In order to get a better understanding of major energy consumption in the selected buildings, general audit have been conducted to collect more detailed information about building operation. Based on MS 1525:2007 any building which implements energy efficient measures can achieved the BEI of 136 kWh/ m2/ year.